Pediatric Gastrostomy Tube Placement: Lessons Learned from High-performing Institutions through Structured Interviews. Issue 2 (March 2017) - Berman, Loren; Hronek, Carla; Raval, Mehul V.; Browne, Marybeth L.; Snyder, Charles L.; Heiss, Kurt F.; Rangel, Shawn J.; Goldin, Adam B.; Rothstein, David H.
Abstract : Introduction: Gastrostomy tube (GT) placement is one of the most common operations performed in children, and it is plagued by high complication rates. Previous studies have shown variation in readmission and emergency room visit rates across different children's hospitals, with both low and high outliers. There is an opportunity to learn how to optimize outcomes by identifying practices at high-performing institutions. Methods: Surgeons and nurses routinely involved in GT care at 8 high-performing pediatric centers were identified. We conducted structured interviews focusing on the approach to GT education, technical aspects of GT placement, and postoperative management. Summary statistics were performed on quantitative data, and the open-ended responses were analyzed by 2 independent reviewers using content analysis. Results: Several common practices among high-performing centers were identified (standardized approach to education, availability by phone and in clinic to manage GT-related issues, and empowering families to feel confident with troubleshooting and dealing with GT problems). There was substantial variation in operative technique and postoperative care. The participants expressed that technical aspects of operative placement and postoperative management of feedings and common complications are not as important as education, availability, and empowerment in optimizing outcomes. Conclusions: We have identified common themes among pediatric centers with favorable outcomes after GT placement. Identifying which components of GT care are associated with optimal outcomes is critical to our understanding of current practice and may help identify opportunities to improve care quality.